CCPS project 246: Second edition of the guidelines for siting and layout of facilities. Issue 2 (31st August 2017) - Vaughen, Bruce K.; Timm, Martin; Connolley, Donald; Cowley, Charles
Abstract : The second edition of the Center for Chemical Process Safety (CCPS) Guidelines for Siting and Layout of Facilities (2017) has been written to address the many developments in the last decade which have improved how companies survey and select new sites, evaluate acquisitions, or expand their existing facilities. By updating the title of the first edition issued in 2003, Guidelines for Facility Siting and Layout, it has been emphasized that this book focuses not only on siting of buildings and unit operations within a facility, but also on siting of facilities within a community. This guideline addresses issues for those involved in business and project development of processes with hazardous materials and energies, provides guidance for facility layout experts, and provides information for authorities and the public involved in the project's approval. In addition, this edition adds discussions on how the life cycle and long‐term risks of the facility are addressed, how toxic dispersions and the effects of explosions are modeled, how changes can be more effectively managed, and how to select the optimal distances between the equipment. This article will provide an overview of the changes to the first edition, as well as provide an overview of the significant reviews and updates to the appendices containing the recommended separation distances and checklists that will help the teams obtain the information they need when locating the project, when arranging the processes, and when arranging the equipment. © 2017 American Institute of Chemical Engineers Process Saf Prog 37: 311–321, 2018